Haplotype analysis reveals that the recurrent BRCA1 deletion of exons 23 and 24 is a Greek founder mutation. Issue 3 (22nd August 2016) - Apostolou, P.; Pertesi, M.; Aleporou‐Marinou, V.; Dimitrakakis, C.; Papadimitriou, C.; Razis, E.; Christodoulou, C.; Fountzilas, G.; Yannoukakos, D.; Konstantopoulou, I.; Fostira, F.
Abstract : A recurrent large genomic rearrangement (LGR) encompassing exons 23 and 24 of the BRCA1 gene has been identified in breast‐ovarian cancer families of Greek origin. Its breakpoints have been determined as c.5406 + 664_*8273del11052 (RefSeq: NM_007294.3) and a diagnostic polymerase chain reaction (PCR) has been set up for rapid screening. In a series of 2, 092 high‐risk families completely screened for BRCA1 and BRCA2 germline mutations, we have found the deletion in 35 families (1.68%), representing 7.83% of the mutations identified in both genes and 10.3% of the total BRCA1 mutations. In order to characterize this deletion as a founder mutation, haplotype analysis was conducted in 60 carriers from 35 families, using three BRCA1 intragenic microsatellite markers and four markers surrounding the BRCA1 locus. Our results demonstrate a common shared core disease‐associated haplotype of 2.89Mb. Our calculations estimate that the deletion has originated from a common ancestor 1450 years ago, which most probably inhabited the Asia Minor area. The particular (LGR) is the third mutation of such type that is proven to have a Greek founder effect in the Greek population, illustrating the necessity for LGRs testing in individuals of Greek descent. Abstract :